Variation of the Labor Force Distribution according to the Economic Activity of the Population of Anbar Province for the Period 1987 – 2011 (Journal of the College of Education for Women, 2019)
This study deals with the Spatial and Periodical Variation of the Economical Activities for thePopulation of Al – Anbar Province on the level of districts , according to the PopulationComputation for the period 1987 and 1997 and the results of determinations and numberingsfor the year of 2011 .This study depends on the Details Classifications of the 17th Activities for 1997 and 2011beside the Triple Classification of the Economical Activities for the three study years .The study proves that there is a spatial and periodical variation on the level of study area , andthat’s because of many factors , one of the most important of them was the distribution ofeconomical siege, as well as the weakness of the security conditions , where the workers inthe agricultural activity is increased for 1997 , and then decreased in 2011 , with theincreasing in industrial field in most of districts in 1997 and 2011 , and that indicates to thedecreasing in Agricultural lands with the increasing in population , and the presence ofrarefaction in the work of industrial plants between their work and stoppage because of thesecurity conditions during the U.S. occupation and the accompanying of conditions thatinfluenced the work of such plants and thus its employees.